Characteristics evaluation of 3 phase induction motors based on an acceleration method with increasing moment of inertia technique - Warachart, Sae Kok; Lumyong, P. (My University, 2003)
There are many methods to evaluate a current-speed and torque-speed characteristic of induction motor such as measured output, acceleration, input, and direct measurement, as shown in IEEE standard 112-1996. In this paper, an acceleration method is proposed as a base method to evaluate the characteristics. By using such method, an increasing moment of inertia technique is used to increase an accelerating time. The calculation of the added moment of inertia for testing is presented. The retardation test method is also used to identify the rotor moment of inertia and the viscous friction coefficient of the test system. Mathematical methodology; RMS calculation and curve fitting technique are used to convert and smooth the data before calculation and analysis. The 1-hp, 3-hp, and 5-hp three-phase induction motor are investigated. The difference of the result between acceleration methods and equivalent circuit calculation is illustrated. Finally, the results from the acceleration test are compared with the test results from loaded test and locked rotor test.
Keywords: Acceleration; Accelerometers; Circuit testing; Current measurement; Friction; Induction motors; Measurement standards; Rotors; System testing; Torque measurement